Santonian‐Campanian dinoflagellate cyst biostratigraphy and paleoenvironment of the Krishna‐Godavari Basin, India. (18th April 2022) - Mishra, Ashish K.; Singh, Arun Deo; Prasad, Vandana
Abstract: The present study deals with the biostratigraphic framework of Late Cretaceous sediments of the subsurface Well (DNG) "A" (2085–1840 m depth) from the Raghavapuram/Chintalapalli Shale of the Krishna‐Godavari Basin and analyzed the palynological assemblage. The recorded palynological assemblage is dominated by marker dinoflagellate cyst viz. Areoligera coronata, Areoligera senonensis, Heterosphaeridium spinaconjunctum, Nelsoniella aceras, Nelsoniella semireticulata, Odontochitina porifera, Xenascus ceratioides, and Xenascus gochtii species. The last occurrence (LO) of significant species of dinoflagellate cysts is considered for the biostratigraphic establishment. On the basis of dinoflagellate cyst biostratigraphy, the examined sequences correspond to the Santonian‐Campanian age. The dominance of gonyaulacoid dinoflagellate cysts is interpreted in terms of sea‐level fluctuation and other paleoenvironmental signals through this biostratigraphic establishment. The recorded dinoflagellate cysts indicate the outer neritic, cool depositional environment. The sea‐level rise, recorded in our study is linked with the transgressive phase during the Late Cretaceous (Santonian‐Campanian) period.